A bridge over troubled water? – Exploring learning processes in a transition program with newly graduated nurses. (February 2021) - Eklund, Annika; Billett, Stephen; Skyvell Nilsson, Maria
Abstract: Successful preparation of newly graduated nurses (NGN) is a critical concern for the healthcare sector. This study explores the learning processes enacted in a transition program with NGNs implemented in hospitals in western Sweden. Group interviews with NGNs and ward managers were conducted, with the data analyzed using qualitative thematic analysis. The following themes were identified as the learning processes secured through the program: Recognizing the NGNs' role as novice practitioners, Emphasizing newly graduated nurses as learners, and Progressing towards a comprehensive nursing role. To support these learning processes, the program should provide opportunies to consolidate and reconcile NGNs' experiences as novices in healthcare environments where effective performance is crucial. If NGNs are supported in these ways, the program can make salient contributions to develop the knowledge bases of their occupational expertise. Highlights: Transitioning from undergraduate education to nursing work practice is a challenging process. Transition programs provide formal arenas for sharing knowledge and learning across sites. Transition programs needs to be integrated into everyday work to support novice practitioners as learners. The everyday work environment and management influence learning processes in transition programs. Several educational components must be addressed for development of occupational expertise.